Révéler les traces du toxique - Benjamin Lysaniuk; Anaïs Ondet; Léa Prost (EchoGéo)
Anaïs Ondet's documentary series Les mauvaises herbes features portraits of women and men suffering from diseases related to the use of agro-pesticides and landscapes cliché of an ordinary countryside where the pathogenic aspect remains – at first sight – invisible. The use of two photographs from this series offers the opportunity, in the context of a dialogue between social sciences and photography, to question the notions of (in)visibility, recognition, memory, trace and banality. The photographer's expression refers to a deep commitment to highlight victims that we do not hear and to focus on landscapes that we no longer notice.